(untitled) - Patterson, Thomas E. (New York, 2003)
Heavily revised in the sixth edition, this descriptive, comprehensive text by Tom Patterson is known for its engaging narrative, future oriented approach, and its ability to tie together the latest scholarship with real-life politics. By using a narrative, The American Democracy weaves together theory, information, and examples in order to bring out key facts and ideas in a way that captures student interest. In the sixth edition, the struggle between liberty and equality is explored in a more extensive and cogent way than in previous editions
Keywords: United States; Politics and government